Analisis Penegakkan Tata Tertib Sekolah Sebagai Sarana Pendidikan Moral di SD Negeri 27 Kenual Nanga Pinoh - Dayang Nani; Mardiana; ahmad Khoiri (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2026)
Abstract: This study aims to analyze the enforcement of school rules as a means of moral education at State Elementary School 27 Kenual, Melawi Regency. The research employed a qualitative method with a descriptive qualitative approach. The research subjects included the principal, teachers, and students. Data were collected through interviews, observations, and documentation, then analyzed using the stages of data reduction, data display, and conclusion drawing, and their validity was tested through technique triangulation. The results show that the enforcement of school rules at SDN 27 Kenual has been implemented consistently and in a structured manner. Teachers play an active role in supervising, reprimanding, and providing educational sanctions, such as requiring students who arrive late to clean the school yard. Teachers’ exemplary discipline further strengthens students’ character formation. The main supporting factors are teacher consistency and parental support, while the inhibiting factors include the low awareness of some students and environmental influences. It is concluded that school rules are effective as a means of moral education, but they still need to be strengthened through synergy among the school, parents, and the community. Keywords: School Rules, Education, Moral. ABSTRAK: Penelitian ini bertujuan menganalisis penegakan tata tertib sekolah sebagai sarana pendidikan moral di Sekolah Dasar Negeri 27 Kenual, Kabupaten Melawi. Penelitian menggunakan metode kualitatif dengan pendekatan deskriptif kualitatif. Subjek penelitian meliputi kepala sekolah, guru, dan siswa. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan, serta diuji keabsahannya melalui triangulasi teknik. Hasil penelitian menunjukkan bahwa penegakan tata tertib di SDN 27 Kenual telah dilaksanakan secara konsisten dan terstruktur. Guru berperan aktif dalam mengawasi, menegur, dan memberikan sanksi yang bersifat mendidik, seperti membersihkan halaman sekolah bagi siswa yang terlambat. Keteladanan guru dalam bersikap disiplin turut memperkuat pembentukan karakter siswa. Faktor pendukung utama ialah konsistensi guru dan dukungan orang tua, sedangkan faktor penghambat meliputi rendahnya kesadaran sebagian siswa dan pengaruh lingkungan. Disimpulkan bahwa tata tertib efektif sebagai sarana pendidikan moral, namun masih perlu diperkuat melalui sinergi sekolah, orang tua, dan masyarakat. Kata Kunci: Tata Tertib, Pendidikan, Moral.